A plasmonic interfacial evaporator for high-efficiency solar vapor generation. Issue 12 (18th October 2018) - Tao, Fujun; Zhang, Yuliang; Yin, Kuan; Cao, Shengjia; Chang, Xueting; Lei, Yanhua; Wang, Dongsheng; Fan, Runhua; Dong, Lihua; Yin, Yansheng; Chen, Xiaobo
Abstract : A novel plasmonic interfacial evaporator composed of Cu9 S5 nanonets and PVDFM has shown high efficiencies of 80.2 ± 0.6% and 91.5 ± 1.1% under 1 and 4 sun irradiation, respectively, for solar vapor generation. Abstract : The increasing energy and environmental concerns have spurred enormous research interest towards developing various renewable energy and sustainable environmental solutions. Photothermal conversion for interfacial solar vapor generation is a promising, green energy technology and efficient route for desalination and purification of seawater, i.e. for those parts where freshwater shortage is a severe concern and clean energy is not available. Eco-friendly, highly efficient and low-cost interfacial evaporators are highly desirable for the practical and widespread application of this technology. In this work, we have demonstrated a novel interfacial evaporator employing Cu9 S5 nanonets with heterogeneous hexagonal holes as the photothermal conversion material and a microporous poly(vinylidene fluoride) membrane (PVDFM) as the supporting material. The Cu9 S5 /PVDFM evaporator displays a broadband (from 250 to 2000 nm) and large (∼91.7%) solar absorptance. The porous structures of Cu9 S5 nanonets and PVDFM facilitate the water transportation, and the large optical absorption of Cu9 S5 /PVDFM converts most of the solar energy to thermal energy, producing water vapor with high efficiency. The Cu9 S5 /PVDFM evaporator exhibits solar vapor generation efficiencies of 80.2 ± 0.6% and 91.5 ± 1.1% under one-sun and four-sun irradiation, respectively, making it among the best copper sulphide-based solar evaporators reported so far. This Cu9 S5 /PVDFM evaporator is reusable, flexible, highly efficient, easy to prepare, easy to scale up, and controllable for tailoring, showing a promising future for interfacial solar vapor generation.